Comparison of four molecular approaches to identify Candida parapsilosis complex species - Leonardo Silva Barbedo; Maria Helena Galdino Figueiredo-Carvalho; Mauro de Medeiros Muniz; Rosely Maria Zancopé-Oliveira (Memorias do Instituto Oswaldo Cruz)
Since the description of Candida orthopsilosis and C. metapsilosis in 2005, several methods have been proposed to identify and differentiate these species from C. parapsilosis sensu stricto. Species-specific uniplex polymerase chain reaction (PCR) was performed and compared with sequencing of the D1/D2 region of the LSU 28S rDNA gene, microsatellite typing of C. parapsilosis sensu stricto, and PCR-restriction fragment length polymorphism patterns in the ITS1-5.8S-ITS2 region of the rDNA gene. There was agreement between results of testing of 98 clinical isolates with the four PCR-based methods, with 59 isolates identified as C. parapsilosis sensu stricto, 37 as C. orthopsilosis, and two as C. metapsilosis.